Development of a new method for determination of total haem protein in fish muscle. (15th April 2015) - Chaijan, Manat; Undeland, Ingrid
Highlights: A new method for total haem protein determination in fish muscle was developed. SDS and heat dissolved the fish muscle and converted haem proteins to hemichrome. Hemichrome had a maximum absorbance at 535 nm. A new method was suited for fresh/frozen fish with ⩽30% lipid, <5% NaCl and pH 5.5–7. Abstract: Using classic haem protein quantification methods, the extraction step in buffer or acid acetone often becomes limiting if muscle is oxidised and/or stored; haem-proteins then tend to bind to muscle components like myofibrils and/or biomembranes. The objective of this study was to develop a new haem protein determination method for fish muscle overcoming such extractability problems. The principle was to homogenise and heat samples in an SDS-containing phosphate buffer to dissolve major muscle components and convert ferrous/ferric haem proteins to hemichromes with a unique absorption peak at 535 nm. Hb-recovery tests with the new and classic methods showed that the new method and Hornsey's method performed significantly better on fresh Hb-enriched cod mince than Brown's and Drabkin's methods; recovery was ⩾98%. However, in highly oxidised samples and in cod protein isolates made with acid pH-shift processing, the new method performed better than Hornsey's method (63% and 87% vs. 50% and 68% recovery). Further, the new method performed well in fish muscle with ⩽30% lipid, <5% NaCl and pH 5.5–7.0; it was also unaffected by freezing/frozen storage.